Evaluasi Sistem HVAC dan Pencahayaan Berdasarkan Lingkungan Dengan Metode Komparatif Terhadap Standarisasi SNI Di Gedung Teknik Elektro Universitas Malikussaleh - Muhammad, Muhammad; Rizki, Dini Indah; Yusdartono, Habib Muharry; Ezwarsyah, Ezwarsyah; Meliala, Selamat (Politeknik Negeri Batam, 2025)
This study aims to evaluate the performance of the HVAC (Heating, Ventilation, and Air Conditioning) system and lighting at the Faculty of Electrical Engineering building, Universitas Malikussaleh, based on environmental factors and compliance with Indonesian National Standards (SNI). This evaluation is essential to ensure comfort, energy efficiency, and the suitability of the learning and working environment at Universitas Malikussaleh. Measurements include temperature, humidity, and light intensity in several rooms. The study results indicate that the temperature in all rooms is within the SNI standard range (22°C to 29°C) but tends to be close to the upper limit, with the highest temperature reaching 30°C in room FT.04.03.05 and the lowest at 26,9°C in the Head of Department's Office. Relative humidity exceeds the SNI standard (40% to 60%), with the highest humidity at 73% in Classroom FT.04.02.05 and the lowest at 63,2% in Meeting Rooms 1, 2, and 3. Light intensity in several rooms, especially classrooms and laboratories, does not meet the standards. This study concludes that although the temperature is relatively within the standard, both humidity and light intensity need to be improved to meet SNI standards.